Desentralisasi Fiskal: Tantangan Pengelolaan Pengeluaran Daerah dalam Mewujudkan Otonomi Keuangan Daerah - Latifa, Asma; Frinaldi, Aldri; Magriasti, Lince; Naldi, Hendra (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
This article provides an in-depth analysis of fiscal decentralization in Indonesia, focusing on regional expenditures as an indicator of local government financial capacity within the framework of regional autonomy. While fiscal decentralization aims to create effective, efficient, and locally responsive governance, the study's findings reveal persistent challenges in its implementation. The descriptive qualitative study, utilizing literature review and case studies, highlights three main issues: the dominance of regional spending by routine expenditures, particularly personnel costs, leading to limited allocations for strategic development and public services ; a high fiscal dependency on central government transfers (DAU, DAK, DBH), which indicates weak fiscal autonomy and disincentivizes local revenue generation; and institutional weaknesses, including rigid budgeting, fragmented regulations, and a lack of competent human resources. These conditions hinder the effectiveness of fiscal decentralization in promoting equitable and sustainable regional development. Therefore, policy reformulation is crucial, emphasizing result-based budgeting, strengthening institutional capacity in planning and oversight, and reforming the intergovernmental fiscal transfer system to be more needs-based and performance-oriented. This work contributes both theoretically and practically to improving local financial governance in the decentralization era.